Towards the Improvement of Chinese Labour Law - A Comparative Analysis of Chinese and South African Collective Labour Law - Jin, Lin (Institute of Development and Labour Law, 2014)
With the expansion of the open market system and globalization, employees increasingly need more protection from the law. So how to properly and efficiently develop a labour law system is becoming an important question for many countries. China is one country facing this issue. Therefore, the purpose of this dissertation is to explore this question. It will examine the weaknesses existing in current Chinese labour law system through a comparative analysis with South Africa's labour law system, establishing the main influences which impact on the Chinese labour law system. Finally, it will demonstrate that the use of legal transplantation would help the Chinese labour law system.